2011
DOI: 10.1016/j.ijsolstr.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

High accuracy wave simulation – Revised derivation, numerical analysis and testing of a nearly analytic integration discrete method for solving acoustic wave equation

Abstract: a b s t r a c tThe nearly analytic integration discrete (NAID) method for solving the two-dimensional acoustic wave equation has been fully mathematically revised, analyzed and tested. The NAID method is an alternative numerical modeling method for generating synthetic seismograms. The acoustic wave equation is first transformed into a system of first-order ordinary differential equations (ODEs) with respect to time variable t, and then directly integrated at a small time interval of [t n , t n+1 ] to obtain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Then, according to Yang et al, (2003, 2006), Tong (2011, 2013) and Lang and Yang, (2017), the discretization of each partial derivative using the NAD method is obtained as:…”
Section: Appendix: 3d Fourth‐order Nad Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, according to Yang et al, (2003, 2006), Tong (2011, 2013) and Lang and Yang, (2017), the discretization of each partial derivative using the NAD method is obtained as:…”
Section: Appendix: 3d Fourth‐order Nad Methodsmentioning
confidence: 99%
“…The nearly analytic discrete (NAD) method is a finite difference method that uses displacement and its gradient to approximate the high‐order partial derivatives in the wave equation (Yang DH et al, 2003, 2004, 2006; Tong P et al, 2011, 2013). As this method captures more detailed wave equation information, dispersion analysis and numerical experiments have shown that it can solve the wave equation more accurately and efficiently than traditional finite difference methods (Yang DH et al, 2010, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To compute the high-order spatial derivatives in the wave equations (12) and (21), we follow Tong et al (2011) and Yang et al (2006Yang et al ( , 2007 and obtain the approximation formulae. For convenience, we list the formulae used in the NETD method as follows:…”
Section: Appendix 1: Approximations Of High-order Spatial Derivativesmentioning
confidence: 99%
“…These NAD operators use only three grid points in a spatial direction to achieve the fourthorder spatial accuracy, and operators can efficiently suppress the numerical dispersion. Based on the idea, a range of different effective numerical algorithms have been proposed by Chen et al (2010), Tong et al (2011), and Ma et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…The three most common types of modelling methods in use in geophysics are direct methods, integral‐equation methods, and asymptotic methods (Carcione, Herman and ten Kroode ). Over the last decade significant progress has been made in all these methods (Etgen and O'Brien ; Wang and Liu ; Hestholm ; Tong, Yang and Hua ; Di Bartolo, Dors and Mansur ; Hobro, Chapman and Robertsson ; Sanyi et al . ).…”
Section: Introductionmentioning
confidence: 99%